PbS doped ZnO nanowires films synthesis by thermal evaporation method: Morphological, structural and optical properties. (May 2021) - Abdallah, B.; Kakhia, M.; Zetoun, W.; Alkafri, N.
Abstract: Thermal evaporation technique has been used to prepare PbS doped ZnO Nanowires films growth on Si (100) and glass substrates. EDX technique was employed to investigate the element's contents of the films materials. Pb and S concentration in the Nanowires films were about at 8% for each one. The XRD pattern showed the structure of ZnO is wurtzite with (002) preferred orientation. Thickness and morphology of the films were explored from cross section of the surface films, respectively, using scanning electron microscopy images. Scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM) images confirmed the ZnO Nanowires and modifications of the morphology when adding PbS. The film deposited without doping (0 ​wt %) was dense structured. However, PbS: ZnO was Nanowires structure. The optical band gap increased with increase the concentrations of PbS. Photoluminescence measurements PL used to estimate band gap for prepared films. Raman and EDX indicate ZnO Nanowires stoichiometry film.